A scorpion-type non-doped organic small molecule hole transport material and its preparation method and application
By designing the scorpion-type non-doped organic small molecule hole transport material DTTP-TPA, the existing doped materials have high prices and poor stability, and the efficient and stable performance of perovskite solar cells has been achieved, with good solubility and Thermal stability.
Patent Information
- Application Number
- CN202211540866.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-01
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-01
AI Technical Summary
Doped organic small molecule hole transport materials used in existing perovskite solar cells have problems such as expensive, poor stability and damage to the perovskite layer, making it difficult to achieve efficient and stable battery performance.
Develop a scorpion-type non-doped organic small molecule hole transport material DTTP-TPA. Through the design of bisthienothienopyrrole and tripaniline structures, the method of spin-coating film is used as a hole transport layer for peritoneum Mine solar cells.
It realizes high-efficiency hole transmission without doping, improves the efficiency and stability of perovskite solar cells, and has good solubility, thermal stability and low cost.
Smart Images

Figure CN116063320B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a scorpion-type non-doped organic small molecule hole transport material and a preparation method and application thereof. Background Art
[0002] Perovskite solar cells (PSCs) as a new type of cell have attracted much attention due to their advantages such as high extinction coefficient, adjustable bandgap, long charge diffusion range, and simple preparation process. The efficiency has increased from 3.8% in 2009 to the current 25.7% (J.Am.Chem.Soc.2009,131,6050;Nature,2021,592,381), which is comparable to silicon cells. The structure of perovskite solar cells mainly includes: transparent conductive glass substrate, electron transport layer, perovskite layer, hole transport layer and metal electrode. Hole transport materials (HTMs) are an important component of perovskite solar cells. On the one hand, they collect and transport holes injected by the perovskite absorption layer to achieve effective electron-hole separation; on the other hand, they improve the Schottky contact between the perovskite layer and the metal electrode to form a good ohmic contact and improve the efficiency of the device (J. Mater. Chem. A, 2018, 6, 18750; J. Mater. Chem. C, 2020, 8, 13415).
[0003] So far, 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) has become the most widely used and successful HTM for achieving high efficiency in PSCs. However, it is expensive, and the original Spiro-OMeTAD film has low conductivity and mobility and requires doping. The hygroscopicity of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and the volatility of 4-tert-butylpyridine (t-BP) in the dopant will destroy the perovskite layer (J.Am.Chem.Soc.2018,140,16720), resulting in its poor stability. Therefore, it is essential to develop a non-doped organic small molecule HTM to prepare efficient and stable PSCs.
[0004] Therefore, we invented a new type of non-doped organic small molecule HTM based on the structure of bithienothienopyrrole (DTTP) and triphenylamine (TPA). This material has the advantages of good planarity, high degree of conjugation, high hole mobility and adjustable energy levels. By spin coating, it was used as a hole transport layer to obtain non-doped solution-processable PSCs. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a scorpion-type non-doped organic small molecule hole transport material and a preparation method and application thereof.
[0006] The present invention provides a scorpion-type non-doped organic small molecule hole transport material, which is a non-doped organic small molecule hole transport material containing dithienothienopyrrole and triphenylamine groups, with dithienothienopyrrole as an acceptor unit, and triphenylamine donor units are introduced into the thiophenes at both ends of the acceptor unit and the middle pyrrole, respectively, to form a scorpion-type non-doped organic small molecule hole transport material. The non-doped organic small molecule hole transport material (DTTP-TPA) has the following structural formula:
[0007]
[0008] The present invention also provides a method for preparing the above-mentioned scorpion-type non-doped organic small molecule hole transport material, comprising the following steps:
[0009] Step 1: react the commercially available raw material thieno[3,2-b]thiophene with n-butyl lithium, and then react with triisopropylsilyl chloride to form a protective group to generate compound I, the structural formula of which is:
[0010]
[0011] Step 2, bromination reaction of compound I with N-bromosuccinimide to generate compound II, the structural formula of compound II is:
[0012]
[0013] Step 3, compound II is first reacted with lithium diisopropylamide, and then coupled with anhydrous copper chloride to generate compound III, the structural formula of compound III is:
[0014]
[0015] Step 4, reacting compound III with tetrabutylammonium fluoride to remove the protecting group to generate compound IV, the structural formula of compound IV is:
[0016]
[0017] Step 5, reacting commercially available raw materials p-methoxyiodobenzene and p-nitroaniline under the catalysis of cuprous iodide, potassium carbonate and L-proline to obtain compound TPA-NO2, the structural formula of the compound TPA-NO2 is:
[0018]
[0019] Step 6, reducing the compound TPA-NO2 and hydrazine hydrate under palladium-carbon catalysis to generate the compound PTA-NH2, wherein the structural formula of the compound TPA-NH2 is:
[0020]
[0021] Step 7, compound IV and compound TPA-NH2 undergo a ring-closing reaction to generate compound DTTP, the structural formula of the compound DTTP is:
[0022]
[0023] Step 8, reacting the compound DTTP with n-butyl lithium, and then reacting with tributyltin chloride to generate compound V, wherein the structural formula of the compound V is:
[0024]
[0025] Step nine, reacting commercially available raw materials 4-bromo-4′,4′-dimethoxytriphenylamine and 2-tributyltinthiophene to generate a compound ThTPA, the structural formula of the compound ThTPA is:
[0026]
[0027] Step 10, reacting the compound ThTPA with N-bromosuccinimide to generate a compound ThTPA-Br, wherein the structural formula of the compound ThTPA-Br is:
[0028]
[0029] Step 11: Compound V and compound ThTPA-Br are subjected to Still coupling reaction under the catalysis of tetrakis(triphenylphosphine)palladium to generate DTTP-TPA.
[0030] The synthetic route of the preparation method of the present invention is as follows:
[0031]
[0032] in,
[0033] The step 1 is: under nitrogen protection and -78°C, thieno[3,2-b]thiophene and n-butyllithium are reacted for 1 to 2 hours, triisopropylsilyl chloride is added to the reaction system for reaction for 0.5 to 1 hour, the temperature is raised to room temperature and the reaction is continued for 8 to 16 hours, and compound I is obtained through separation and purification; the molar ratio of thieno[3,2-b]thiophene, n-butyllithium and triisopropylsilyl chloride is 1:1 to 1.1:1 to 1.2.
[0034] The step 2 is: reacting compound I with N-bromosuccinimide for 2 to 3 hours at 0°C in a light-proof condition, then heating to room temperature and continuing the reaction for 8 to 16 hours, and obtaining compound II through separation and purification; the molar ratio of compound I to N-bromosuccinimide is 1:1 to 1.2.
[0035] The step three is: under nitrogen protection and -78°C, compound II is reacted with lithium diisopropylamide for 1 to 2 hours, anhydrous copper chloride is added to the reaction system for 0.5 to 1 hour, the temperature is raised to room temperature and the reaction is continued for 8 to 16 hours, and compound III is obtained by separation and purification; the molar ratio of compound II, lithium diisopropylamide and anhydrous copper chloride is 1:1 to 1.4:1 to 1.3.
[0036] The step 4 is: under nitrogen protection and 0°C, compound III is reacted with tetrabutylammonium fluoride for 2 to 3 hours, the temperature is raised to room temperature and the reaction is continued for 8 to 16 hours, and compound IV is obtained through separation and purification; the molar ratio of compound III to tetrabutylammonium fluoride is 1:2 to 2.2.
[0037] The step five is: under nitrogen protection and 115° C., p-methoxyiodobenzene and p-nitroaniline are reacted for 48 to 96 hours under the catalysis of cuprous iodide, potassium carbonate and L-proline, and compound TPA-NO2 is obtained through separation and purification; the molar ratio of p-nitroaniline, p-methoxyiodobenzene, cuprous iodide, potassium carbonate and L-proline is 1:2 to 4:0.25:7.8:0.8.
[0038] The step six is: under nitrogen protection and 80° C., compound TPA-NO2 is reacted with hydrazine hydrate under palladium-carbon catalysis for 8 to 16 hours, and compound TPA-NH2 is obtained after separation and purification; the molar ratio of compound TPA-NO2, hydrazine hydrate and palladium-carbon is 1:5 to 10:0.4.
[0039] The step seven is: under nitrogen protection and 110° C., compound IV and compound TPA-NH2 are reacted for 8 to 16 hours under the catalysis of sodium tert-butoxide, tris(dibenzylideneacetone)dipalladium and 1,1′-bis(diphenylphosphino)ferrocene, and compound DTTP is obtained after separation and purification; the molar ratio of compound IV, compound TPA-NH2, sodium tert-butoxide, tris(dibenzylideneacetone)dipalladium and 1,1′-bis(diphenylphosphino)ferrocene is 1:1 to 1.5:15:0.08:0.16.
[0040] The step eight is: under nitrogen protection and -78°C, reacting the compound DTTP with n-butyl lithium for 1 to 2 hours, adding tributyltin chloride to the reaction system for 0.5 to 1 hour, heating to room temperature and continuing to react for 8 to 16 hours, and obtaining compound V through separation and purification; the molar ratio of the compound DTTP, n-butyl lithium and tributyltin chloride is 1:2 to 2.5:2 to 2.5.
[0041] The step nine is: under nitrogen protection and 110° C., 4-bromo-4′,4′-dimethoxytriphenylamine and 2-tributyltinthiophene are reacted under the catalysis of tetrakis(triphenylphosphine)palladium for 8 to 16 hours, and compound ThTPA is obtained after separation and purification; the molar ratio of 4-bromo-4′,4′-dimethoxytriphenylamine, 2-tributyltinthiophene and tetrakis(triphenylphosphine)palladium is 1:1 to 2:0.02.
[0042] The step ten is: at 0°C, react the compound ThTPA with N-bromosuccinimide in a light-proof condition for 2 to 3 hours, then heat to room temperature and continue the reaction for 8 to 16 hours, and obtain the compound ThTPA-Br after separation and purification; the molar ratio of the compound ThTPA to N-bromosuccinimide is 1:1 to 1.5.
[0043] The step eleven is: under nitrogen protection and 110° C., compound V and compound ThTPA-Br are reacted under the catalysis of tetrakis(triphenylphosphine)palladium for 8 to 16 hours, and compound DTTP-TPA is obtained after separation and purification; the molar ratio of compound V, compound ThTPA-Br and tetrakis(triphenylphosphine)palladium is 1:2 to 2.5:0.05.
[0044] The present invention also provides an application of the above-mentioned scorpion-type non-doped organic small molecule hole transport material, wherein the non-doped organic small molecule hole transport material DTTP-TPA is used in perovskite solar cells.
[0045] The perovskite solar cell comprises a perovskite layer, a hole transport layer, an electron transport layer and an electrode, and the hole transport layer adopts the above-mentioned non-doped organic small molecule hole transport material DTTP-TPA.
[0046] Wherein, the preparation of the perovskite solar cell comprises the following steps:
[0047] Step 1, spin coating a layer of tin dioxide on the indium tin oxide conductive glass as an electron transport layer;
[0048] Step 2, spin coating a layer of perovskite precursor solution on the electron transport layer as a perovskite layer;
[0049] Step 3, spin coating a layer of non-doped organic small molecule hole transport material on the perovskite layer as a hole transport layer;
[0050] Step 4: evaporate metallic silver on the hole transport layer as an electrode, or evaporate MoO3 and silver as a composite electrode.
[0051] Beneficial effects of the present invention:
[0052] Compared with the disclosed functionalized hole transport materials, the hole transport material DTTP-TPA provided by the present invention has the following advantages:
[0053] (1) DTTP-TPA uses a dithienothienopyrrole structure as the core. This structure is an extended conjugation on the common dithienopyrrole (DTP) structure, which has better planarity and conjugation, and can effectively improve hole mobility and conductivity, thereby achieving non-doping;
[0054] (2) The introduction of triphenylamine groups on the nitrogen atom of pyrrole in this material can, on the one hand, adjust the energy level, solubility and control the planar shape of the molecule; on the other hand, traditional linear hole transport materials generally have two donor units. This material adds a triphenylamine donor unit on the nitrogen atom of pyrrole to regulate the interaction between the donor and the acceptor, thereby improving the performance of the hole transport material.
[0055] (3) The material preparation method has a high synthesis yield, the raw materials are easily available, and the cost is low;
[0056] (4) The material has good solubility, thermal stability and large contact angle, which can meet the requirements of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0058] Figure 1 This is a UV-visible light absorption spectrum (UV) of the non-doped organic small molecule hole transport material DTTP-TPA film prepared in an embodiment of the present invention;
[0059] Figure 2 The cyclic voltammetry (CV) diagram of the non-doped organic small molecule hole transport material DTTP-TPA prepared in the embodiment of the present invention;
[0060] Figure 3 Thermogravimetric (TGA) test results of the non-doped organic small molecule hole transport material DTTP-TPA prepared in the embodiment of the present invention;
[0061] Figure 4This is a current-voltage (JV) curve of the perovskite solar cell prepared according to an embodiment of the present invention. DETAILED DESCRIPTION
[0062] The following are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
[0063] Example
[0064] A scorpion-type non-doped organic small molecule hole transport material (DTTP-TPA) has the following chemical structure:
[0065]
[0066] The preparation method of the above-mentioned scorpion-type non-doped organic small molecule hole transport material has the following reaction formula:
[0067]
[0068] The present invention provides a scorpion-type non-doped organic small molecule hole transport material, which is prepared by the following steps:
[0069] Step 1, synthesis of compound I: n-butyl lithium (2.5M, 31.4mL, 78.4mmol) was slowly added dropwise to a solution of commercially available thieno[3,2-b]thiophene (10g, 71.3mmol) in anhydrous tetrahydrofuran (THF, 300mL) at -78°C and nitrogen, and then stirred for 1 hour. Triisopropyl chlorosilane (6.70mL, 31.4mmol) was added dropwise to the solution, reacted for 30 minutes, and then the resulting reactant was warmed to room temperature and stirred overnight. The reaction was then quenched with water, extracted with dichloromethane (DCM), dried with anhydrous magnesium sulfate (MgSO4), filtered and concentrated. The crude product was purified by column chromatography using n-hexane as eluent to obtain compound I (20.0g, 95%) as a white solid. 1 H NMR (400MHz, CDCl3) δ7.70 (d, J=5.1Hz, 1H), 7.56 (s, 1H), 7.41 (d, J=5.1Hz, 1H), 1.35 (m, 3H), 1.09 (d, J=7.3Hz, 18H).
[0070] Step 2, synthesis of compound II: At 0°C, N-bromosuccinimide (13.2 g, 74.2 mmol) was slowly added to a solution of compound I (20.0 g, 67.4 mmol) in anhydrous THF (250 mL), and then the reactant was covered with aluminum foil and stirred overnight. The reaction was quenched with water, extracted with DCM, dried over anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane as eluent to obtain white solid compound II (24.0 g, 94%). 1 H NMR (400MHz, CDCl3) δ7.35 (s, 2H), 1.46-1.41 (m, 3H), 1.20 (d, J=8Hz, 18H).
[0071] Step 3, the synthesis of compound III: under nitrogen protection and -78 ℃, lithium diisopropylamide (2M, 3.8mL, 7.6mmol) was added dropwise to a solution of compound II (2.0g, 5.3mmol) in anhydrous THF (30mL), and the resulting solution was stirred for 1 hour. Anhydrous cupric chloride (0.92g, 6.8mmol) was added quickly, and the reaction mixture was stirred for another 30 minutes. The reactant was then warmed to room temperature and stirred overnight. The reaction was quenched with water, extracted with DCM, dried with anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane as eluent to obtain light yellow solid compound III (1.4g, 70%). 1 H NMR (400MHz, CDCl3) δ7.42 (s, 2H), 1.45-1.33 (m, 6H), 1.15 (d, J=7.1Hz, 36H).
[0072] Step 4, synthesis of compound IV: Tetrabutylammonium fluoride (1M, 2.7mL, 2.7mmol) was added dropwise to a solution of compound III (1.0g, 1.3mmol) in anhydrous THF (40mL) at 0°C and nitrogen, and the resulting reactant was warmed to room temperature and stirred overnight. The reaction was quenched with water, extracted with DCM, dried over anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane as eluent to obtain a light yellow solid compound IV (0.46g, 81%). 1 H NMR (400MHz, CDCI3) δ7.50 (d, J=16.2Hz, 2H), 7.32 (d, J=18.4Hz, 2H). 13 C NMR (101MHz, CDCl3) δ141.23, 138.44, 130.37, 128.50, 120.26, 105.20.
[0073] Step 5, synthesis of compound TPA-NO2: Under nitrogen, commercially available p-methoxyiodobenzene (33 g, 140 mmol), p-nitroaniline (5 g, 36.2 mmol), cuprous iodide (1.7 g, 9 mmol), potassium carbonate (38 g, 280 mmol) and L-proline (3.3 g, 29 mmol) were dissolved in anhydrous N, N-dimethylformamide (200 mL) and stirred at 115°C for 4 days. The reaction was cooled to room temperature, quenched with water, extracted with DCM, dried with anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane: DCM = 3: 1 as the eluent, and the obtained crude product was recrystallized from chloroform / n-hexane to obtain an orange-red solid compound TPA-NO2 (8.2 g, 65%). 1 H NMR (400MHz, CDCl3) δ7.99 (d, J=8Hz, 2H), 7.13 (d, J=8Hz, 4H), 6.91 (d, J=12Hz, 4H), 6.75 (d, J=8Hz, 2H).
[0074] Step 6, synthesis of compound TPA-NH2: Under nitrogen, compound TPA-NO2 (0.7 g, 2 mmol) and palladium carbon (5%, 87 mg, 4 mol%) were dissolved in anhydrous ethanol (20 mL), stirred and refluxed at 78 ° C for 1 hour, then slightly cooled, hydrazine hydrate (80%, 2 mL, 17 mmol) was added under nitrogen, and refluxed for 8 hours. After the reaction was completed, it was cooled to room temperature, palladium carbon was filtered off, and the filtrate was concentrated and vacuum dried overnight to obtain a white viscous liquid compound TPA-NH2 (0.6 g, 94%). 1 H NMR (400MHz, DMSO-d6) δ6.80 (s, 8H), 6.71 (d, J=8.6Hz, 2H), 6.52 (d, J=8.6Hz, 2H), 4.89 (s, 2H), 3.69 (s, 6H).
[0075] Step 7, synthesis of compound DTTP: Under nitrogen, compound TPA-NH2 (0.6 g, 1.9 mmol), compound IV (0.7 g, 1.7 mmol), sodium tert-butoxide (2.4 g, 25.5 mmol), tris[dibenzylideneacetone]dipalladium (125 mg, 8 mol%) and 1,1′-bis(diphenylphosphino)ferrocene (150 mg, 16 mol%) were dissolved in anhydrous toluene (40 mL) and stirred under reflux overnight at 110° C. The reaction was cooled to room temperature, quenched with water, extracted with DCM, dried with anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane: DCM=3:1 as eluent to obtain a yellow solid compound DTTP (0.72 g, 72%). 1H NMR (400MHz, CDCl3) δ7.47 (d, J=8.7Hz, 2H), 7.40-7.06 (m, 10H), 6.92 (d, J=8.8Hz, 4H), 3.84 (s, 6H).
[0076] Step 8, synthesis of compound V: n-butyl lithium (2.5M, 0.52mL, 1.3mmol) was slowly added dropwise to a solution of compound DTTP (0.3g, 0.51mmol) in anhydrous THF (20mL) under nitrogen and -78°C, and then stirred for 1 hour. Tributyltin chloride (0.35mL, 1.3mmol) was added dropwise to the solution, stirred for 30 minutes, and then the resulting reactant was warmed to room temperature and stirred overnight. The reaction was then quenched with water, extracted with dichloromethane (DCM), dried with anhydrous MgSO4, filtered and concentrated. No purification was required, vacuum dried to obtain compound V. 1 H NMR (400MHz, CDCl3) δ7.50 (d, J=8.8Hz, 2H), 7.27 (s, 2H), 7.18 (t, J=9.4Hz, 6H), 6.89 (d, J=8.9Hz, 4H), 3.82 (s, 6H).
[0077] Step nine, synthesis of compound ThTPA: Under nitrogen, commercially available 4-bromo-4', 4'-dimethoxytriphenylamine (2g, 5.2mmol), 2-tributyltinthiophene (3g, 10.4mmol) and tetrakis(triphenylphosphine)palladium (120mg, 2mol%) were dissolved in anhydrous toluene (40mL) and stirred at reflux overnight at 110°C. The reaction was cooled to room temperature, quenched with water, extracted with DCM, dried with anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane: DCM = 4: 1 as eluent to obtain a white solid compound ThTPA (1.7g, 85%). 1 H NMR (400MHz, DMSO-d6) δ7.45 (d, J=8.7Hz, 2H), 7.41 (d, J=5.1Hz, 1H), 7.31 (d, J=2Hz , 1H), 7.09-7.01 (m, 5H), 6.92 (d, J=9.0Hz, 4H), 6.78 (d, J=8.7Hz, 2H), 3.74 (s, 6H).
[0078] Step 10, synthesis of compound ThTPA-Br: At 0°C, N-bromosuccinimide (0.77 g, 4.3 mmol) was slowly added to a solution of compound ThTPA (1.5 g, 3.9 mmol) in anhydrous THF (30 mL), and then the reactant was covered with aluminum foil and stirred overnight. The reaction was quenched with water, extracted with DCM, dried over anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane: DCM = 4: 1 as eluent to obtain a light yellow viscous liquid compound ThTPA-Br (1.8 g, 99%). 1 H NMR (400MHz, CDCl3) δ7.34-7.23 (m, 2H), 7.07 (s, 4H), 6.98 (d, J=6.0Hz, 1H), 6.95-6.60 (m, 7H), 3.80 (d, J=6.0Hz, 6H).
[0079] Step 11, synthesis of compound DTTP-TPA: Under nitrogen, compound ThTPA-Br (0.54 g, 1.2 mmol), compound V (0.5 mmol) and tetrakis (triphenylphosphine) palladium (29 mg, 5 mol%) were dissolved in anhydrous toluene (20 mL) and stirred at 110° C. for overnight reflux. The reaction was cooled to room temperature, quenched with water, extracted with DCM, dried over anhydrous MgSO4, filtered and concentrated. The crude product was purified by column chromatography using n-hexane: DCM = 1: 1 as eluent to obtain an orange-red solid compound DTTP-TPA (0.4 g, 59%). 1 H NMR (400MHz, CDCl3) δ7.47-7.38 (m, 4H), 7.32 (s, 2H), 7.22 (d, J=8.6Hz, 5H), 7.17 (d, J=8.5Hz, 3H), 7.09 (dd, J=14.8, 8.5Hz, 10H), 6.92 (d, J=8.1Hz, 9H), 6.85 (dd, J=8.5, 4.7Hz, 9H), 3.82 (s, 6H), 3.81 (s, 12H). 13 C NMR (101MHz, THF-d8) δ156.90, 156.51, 140.47, 140.20, 128.98, 127.26, 127.12, 126.61, 125.90, 124.54, 120.07, 119.54, 114.77, 114.65, 114.56, 54.64.LC-TOF MS(C 80 H 60 N4O6S6) Theoretical value: 1364.2837, measured: 1364.8101.
[0080] The UV-visible absorption spectrum of the compound DTTP-TPA film prepared in this example is shown in Figure 1 , it can be seen that its absorption peak is between 400 and 550nm, which can form a wider band gap. Figure 2 This is the cyclic voltammetry (CV) diagram of DTTP-TPA. Its HOMO energy level is calculated to be -4.93 eV, which has a good energy level match with perovskite. Figure 3 This is the thermogravimetric (TGA) test result of DTTP-TPA. The decomposition temperature is 345°C, which shows good thermal stability.
[0081] The DTTP-TPA prepared in this example is used in a perovskite solar cell. The perovskite solar cell is composed of a perovskite layer, a hole transport layer, an electron transport layer and an electrode, wherein the hole transport layer uses the non-doped organic small molecule hole transport material DTTP-TPA prepared in this example.
[0082] The preparation of perovskite solar cells includes the following steps:
[0083] Step 1: Spin-coat a 2.67 wt % SnO 2 nanoparticle solution at 4000 rpm for 30 seconds to deposit a uniform and dense SnO 2 layer on the ITO conductive glass, and anneal in ambient air at 150° C. for 30 minutes.
[0084] Step 2: 691.5 mg / mL Pbl2 was dissolved in DMF / DMSO (9:1) mixed solvent and spin-coated onto SnO2 at 1500 rpm for 30 seconds, followed by annealing at 70°C for 1 minute to form a Pbl2 film. After the Pbl2 film was cooled to room temperature, a solution of FAI:MAI:MACI (90 mg:6.39 mg:9 mg, dissolved in 1 mL of isopropanol) was spin-coated at 2000 rpm for 30 seconds, followed by annealing at 150°C for 15 minutes under ambient air conditions (30-40% relative humidity) for perovskite growth to form a perovskite layer. The sample was then transferred to a glove box in a nitrogen atmosphere for further processing.
[0085] Step three, 15 mg of non-doped organic small molecule hole transport material DTTP-TPA was added to 0.5 mL of chlorobenzene and stirred at 50° C. for 6 hours, and spin-coated onto the perovskite layer at 3000 rpm for 30 seconds to deposit a hole transport layer (HTL).
[0086] Step 4: Finally, at 5×10 -5 10nm MoO3 and 100nm thick silver electrodes were thermally evaporated under 10 Torr pressure.
[0087] The structure of the prepared perovskite solar cell is: ITO / SnO2 / perovskite / HTL / MoO3 / Ag. The cathode area is defined as the effective active area of the device, which is 0.04 cm 2 , a surface profiler was used to measure the thickness of each spin-coated layer, a thickness / speed meter (Model STM-100) produced by SyconInstrument was used to control the deposition speed and thickness, and a Keithley2400 was used to measure the current-voltage (JV) characteristics of the device, such as Figure 4 The thermal stability of the hole transport material was determined using Diamond TG / DTA from PE, the UV absorption spectrum was measured using U-3310 from Hitachi, and the redox potential was measured using CHI660A.
[0088] The perovskite solar cell prepared with the compound DTTP-TPA prepared in the example as the hole transport layer has a current density of 24.44 mA / cm 2 , the open circuit voltage is 0.82V and the photoelectric conversion efficiency is 16.85%.
[0089] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A scorpion-type non-doped organic small molecule hole transport material, characterized in that: The non-doped organic small molecule hole transport material uses dithienothienopyrrole as an acceptor unit, and introduces triphenylamine donor units on the two end thiophenes and the middle pyrrole of the acceptor unit to form a scorpion-type non-doped organic small molecule hole transport material DTTP-TPA, whose structural formula is as follows:
2. The method for preparing a scorpion-type non-doped organic small molecule hole transport material according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, under nitrogen protection and sub-zero low temperature environment, thieno[3,2-b]thiophene is reacted with n-butyllithium, and triisopropylsilyl chloride is added, and the protective group is reacted at low temperature and then at room temperature to generate compound I, wherein the structural formula of compound I is: Step 2, in a light-proof condition, compound I is subjected to bromination reaction with N-bromosuccinimide at a temperature of 0° C. and then at room temperature to generate compound II, wherein the structural formula of compound II is: Step 3, under nitrogen protection and sub-zero low temperature environment, compound II is first reacted with lithium diisopropylamide, and then coupled with anhydrous copper chloride at low temperature and then room temperature to generate compound III, wherein the structural formula of compound III is: Step 4, under nitrogen protection, compound III is reacted with tetrabutylammonium fluoride at a temperature of 0°C and then at room temperature to remove the protective group to generate compound IV, the structural formula of which is: Step 5, under nitrogen protection and heating environment, p-methoxy iodobenzene and p-nitroaniline are reacted under the catalysis of cuprous iodide, potassium carbonate and L-proline to obtain compound TPA-NO2, the structural formula of the compound TPA-NO2 is: Step 6, under nitrogen protection and heating environment, compound TPA-NO2 and hydrazine hydrate are reduced under palladium carbon catalysis to generate compound PTA-NH2, the structural formula of the compound TPA-NH2 is: Step 7, under nitrogen protection and heating environment, compound IV, compound TPA-NH2, sodium tert-butoxide, tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphino)ferrocene are subjected to ring-closing reaction to generate compound DTTP, the structural formula of the compound DTTP is: Step 8, reacting the compound DTTP with n-butyl lithium under nitrogen protection and sub-zero low temperature environment, then adding tributyltin chloride, and reacting at low temperature first and then at room temperature to generate compound V, wherein the structural formula of compound V is: Step nine, under nitrogen protection and heating environment, 4-bromo-4',4'-dimethoxytriphenylamine, 2-tributyltinthiophene and tetrakis(triphenylphosphine)palladium are reacted to generate a compound ThTPA, the structural formula of the compound ThTPA is: Step 10, the compound ThTPA and N-bromosuccinimide react at a temperature of 0°C and then at room temperature to generate a compound ThTPA-Br, the structural formula of the compound ThTPA-Br is: Step 11: Under nitrogen protection and heating conditions, compound V and compound ThTPA-Br are subjected to Still coupling reaction with tetrakis(triphenylphosphine)palladium as the catalyst to generate DTTP-TPA.
3. The method for preparing a scorpion-type non-doped organic small molecule hole transport material according to claim 2, characterized in that: In the step 1, the molar ratio of thieno[3,2-b]thiophene, n-butyl lithium and triisopropylsilyl chloride is 1:1-1.1:1-1.2; In the step 2, the molar ratio of compound I to N-bromosuccinimide is 1:1 to 1.2; In the step 3, the molar ratio of compound II, lithium diisopropylamide and anhydrous cupric chloride is 1:1-1.4:1-1.3; In the step 4, the molar ratio of compound III to tetrabutylammonium fluoride is 1:2 to 2.2; In the step 5, the molar ratio of p-nitroaniline, p-methoxyiodobenzene, cuprous iodide, potassium carbonate and L-proline is 1:2-4:0.25:7.8:0.8; In the step 6, the ratio of the amount of the compound TPA-NO2, hydrazine hydrate and palladium carbon is 1:5 to 10:0.4; In the step 7, the ratio of the amount of compound IV, compound TPA-NH2, sodium tert-butoxide, tris(dibenzylideneacetone)dipalladium and 1,1'-bis(diphenylphosphino)ferrocene is 1:1-1.5:15:0.08:0.16; In the step eight, the molar ratio of the compound DTTP, n-butyl lithium and tributyltin chloride is 1:2-2.5:2-2.5; In the step nine, the ratio of the amount of 4-bromo-4',4'-dimethoxytriphenylamine, 2-tributyltinthiophene and tetrakis(triphenylphosphine)palladium is 1:1 to 2:0.02; In the step 10, the molar ratio of the compound ThTPA to N-bromosuccinimide is 1:1 to 1.5; In the step eleven, the molar ratio of compound V, compound ThTPA-Br and tetrakis(triphenylphosphine)palladium is 1:2 to 2.5:0.
05.
4. The use of the scorpion-type non-doped organic small molecule hole transport material as claimed in claim 1, characterized in that: The non-doped organic small molecule hole transport material according to claim 1 is used for a perovskite solar cell, wherein the perovskite solar cell comprises a perovskite layer, a hole transport layer, an electron transport layer and an electrode, and the hole transport layer adopts the non-doped organic small molecule hole transport material DTTP-TPA.
5. The use of a scorpion-type non-doped organic small molecule hole transport material according to claim 4, characterized in that: The method for preparing the perovskite solar cell comprises the following steps: (1) Spin coating a layer of tin dioxide on the indium tin oxide conductive glass as an electron transport layer; (2) spin coating a layer of perovskite precursor solution on the electron transport layer as a perovskite layer; (3) spin coating a layer of the non-doped organic small molecule hole transport material DTTP-TPA on the perovskite layer as a hole transport layer; (4) On the hole transport layer, metallic silver is evaporated as an electrode or molybdenum oxide and silver are evaporated as a composite electrode.
Citation Information
Patent Citations
Linear organic hole transport material and preparation and application thereof
CN109265470A
Doping-free hole transport material based on indeno[1,2-b]carbazole, and synthesis method and application thereof
CN111187280A